An Unusual Lingual Ulcerated Capillary Angioma After Dressmaker Needle Trauma, Above Migratory Glossitis Lesion, in a Patient With a History of Cancer: A Case Report - Cinzia Casu; Andrea Butera; Clara Gerosa; Andrea Scribante; Martina Salvatorina Murgia; Germano Orrù (Case Reports in Dentistry)
Vascular malformations are relatively common benign proliferative lesions of vascular and connective tissue origin that can present in oral regions, such as on the tongue. Etiological factors include genetic mutations or molecular changes related to syndromes, trauma, vascular wall resistance to blood flow, and may form part of other systemic diseases. Clinically, they can be extremely heterogeneous, and they can also cause important diagnostic doubts. Migratory glossitis is a very common oral condition in the general population, linked to immunological factors, sometimes connected with intestinal health problems. The aim of this work is to report an atypical case of ulcerated angioma on the tongue and the contemporary presence of migratory glossitis. A 54-year-old Caucasian female with a history of an intestinal cancer presented a particular exophytic lesion on the tip of the tongue where the hypothetical diagnosis of oral metastasis had been included, also for the rapid onset of the oral lesion. The dressmaker’s needle trauma related to the patient’s work activity could have been the triggering factor for the appearance of the neoformation. The diagnosis after histological evaluation was ulcerated capillary angioma. Due to the unusual presentation of this type of lesion, it is needed to reconsider current knowledge on the etiopathogenesis of vascular lesions and its clinical inclusion in the differential diagnosis.